SMOOTH SAILING TO SAVE HAVEN OF ISLAM: A Study of Chinese Descendants Converting to Islam in Watan Soppeng (State Islamic University (UIN) of Sunan Ampel Surabaya, 2025)
Contrary to what happened elsewhere in Indonesia, conversion of Chinese descents to Islam in Wattan Soppeng is considered peaceful and more numerous. While religious conversions sometimes followed by family disputes and often breakup, this article shows the gradual and peaceful conversion to Islam of the Chinese in Watan Soppeng. It also uncovers the origin of the Chinese conversion to Islam, the motives, and the relationship between Chinese Muslim converts and local indigenous people. This study applied three methods to obtain data and information, namely in-depth interviews, observation, and documentation studies. The data and information obtained were verified, classified, integrated, and described. The research results show that the conversion process began in the 1950s and has been lasting for approximately seventy years. This conversion was caused by some reasons, namely the interest in Islamic teachings, the motive of marriage, and the self-awareness to convert to Islam. So far, the native Chinese have maintained good relations with the local Bugis community. Those who embraced Islam enjoyed more intensive social interactions.